2011
DOI: 10.1213/ane.0b013e31820568af
|View full text |Cite
|
Sign up to set email alerts
|

The Novel Role of the Mu Opioid Receptor in Lung Cancer Progression

Abstract: Background The possibility that mu opioid agonists can influence cancer recurrence is a subject of recent interest. Epidemiologic studies suggested that there were differences in cancer recurrence in breast and prostate cancer contingent on anesthetic regimens. In this study, we identify a possible mechanism for these epidemiologic findings based on mu opioid receptor (MOR) regulation of Lewis lung carcinoma (LLC) tumorigenicity in cell and animal models. Methods We utilized human lung tissue and human non-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
199
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 230 publications
(223 citation statements)
references
References 47 publications
7
199
1
7
Order By: Relevance
“…52 The theory regarding MOR involvement in metastasis is further supported by the diminished progression of lung carcinoma in MOR knockout mice treated with the opioid receptor antagonist naltrexone. 53 Morphine does not influence the initiation of tumour development; rather, it affects the progression of established breast tumour, as recently shown in a transgenic mouse study that found significantly decreased survival in a mouse model of breast adenocarcinoma. 54 In the same study, it was found that morphine promoted lymphangiogenesis, mast cell activation and degranulation, and increased levels of inflammatory cytokines, tryptase, and substance P. In addition, the morphine-treated mice had increased tumour burden and decreased duration of survival.…”
Section: Opioidsmentioning
confidence: 91%
“…52 The theory regarding MOR involvement in metastasis is further supported by the diminished progression of lung carcinoma in MOR knockout mice treated with the opioid receptor antagonist naltrexone. 53 Morphine does not influence the initiation of tumour development; rather, it affects the progression of established breast tumour, as recently shown in a transgenic mouse study that found significantly decreased survival in a mouse model of breast adenocarcinoma. 54 In the same study, it was found that morphine promoted lymphangiogenesis, mast cell activation and degranulation, and increased levels of inflammatory cytokines, tryptase, and substance P. In addition, the morphine-treated mice had increased tumour burden and decreased duration of survival.…”
Section: Opioidsmentioning
confidence: 91%
“…This study also found that when the MOR expression and opioid requirement were included in the multivariate model, the significance of other known prognostic variables diminished considerably. It was also found that injecting Lewis lung cancer cells into nude MOR knockout mice did not result in the growth of a tumor while it almost invariably did in the case of normal mice [47]. The in vitro work of Ecimovic et al [48] demonstrated that morphine increases the migration of both estrogen positive and negative breast cancer cells in a dose-dependent way by 17-27 %.…”
Section: Opioidsmentioning
confidence: 98%
“…Значительное уменьшение коли-чества опиоидных аналгетиков и качество обез-боливания у пациентов онкологического профи-ля за счет использования регионарных методик особенно актуально, так как снижается выра-женность отрицательных эффектов наркотиче-ских препаратов, в том числе угнетение иммуни-тета и устойчивости к метастазированию. Дока-зано прямое влияние агонистов µ-опиатных ре-цепторов на развитие и прогрессию рака [4,5]. Показано, что механическое повреждение вызы-вает подавление активности естественных кил-леров и распространение опухолевого процесса в эксперименте [6].…”
Section: Introductionunclassified